(untitled) (Impact: Journal of Transformation, 2023)
1 John 1:5-10 is an exhortatory piece whose subject is the character of Christian living in relation to God’s standard of holiness. This paper is a study of the necessity of walking in the light based on the exegesis of 1 John 1:5-10. The exegesis applies the grammatical-historical method through which the researcher examines the grammar, syntax, and the literary structure of 1 John 1:5-10. The statement, ὁ θεὸς φῶς ἐστιν καὶ σκοτία ἐν αὐτῷ οὐκ ἔστιν οὐδεμία, in verse 5 and its related concepts in the other verses serves as the central idea under investigation. The researcher observes that the author uses a pastoral rhetoric method to warn against three negative claims and practices (1 Jn 1:6, 8, 10) and encourages his audience to observe two positive confessions and practices (1 Jn 1:7, 9), all of which are related to verse 5. The exegesis shows that the aim of the author is to encourage believers to live according to the fact that God is light and requires that those who have fellowship with him should walk in the light (1 Jn 1:5-7). This article has highlighted some of the ways in which Christians today can be motivated to pursue a holy life as a requirement by God in order to conform to his nature.